1993
DOI: 10.1007/bf00419608
|View full text |Cite
|
Sign up to set email alerts
|

The role of attention for the Simon effect

Abstract: It has been claimed that spatial attention plays a decisive role in the effect of irrelevant spatial stimulus-response correspondence (i.e., the Simon effect), especially the way the attentional focus is moved onto the stimulus (lateral shifting rather than zooming). This attentional-movement hypothesis is contrasted with a referential-coding hypothesis, according to which spatial stimulus coding depends on the availability of frames or objects of reference rather than on certain attentional movements. In six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
211
6
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(246 citation statements)
references
References 45 publications
27
211
6
2
Order By: Relevance
“…By manipulating response time with respect to the irrelevant movement stimulus, it was possible to investigate the build-up and/or decay of the spatial compatibility and imitative compatibility effects over time within a trial. Hommel (1993;1994), in a spatial compatibility task, presented the discriminative stimulus 196 ms after the irrelevant spatial stimulus. This manipulation delayed the response time with respect to the processing of the irrelevant spatial stimulus, which resulted in a reduced spatial compatibility effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By manipulating response time with respect to the irrelevant movement stimulus, it was possible to investigate the build-up and/or decay of the spatial compatibility and imitative compatibility effects over time within a trial. Hommel (1993;1994), in a spatial compatibility task, presented the discriminative stimulus 196 ms after the irrelevant spatial stimulus. This manipulation delayed the response time with respect to the processing of the irrelevant spatial stimulus, which resulted in a reduced spatial compatibility effect.…”
Section: Methodsmentioning
confidence: 99%
“…Hommel's (1993;1994) data suggested that a delay of 196 ms between the onset of the irrelevant movement stimulus and the discriminative stimulus was sufficient for the decay of the spatial compatibility effect. In order to investigate the intermediate stages of this decay, levels of offset giving delays of 80 ms and 160 ms were chosen whereby the discriminative stimulus was presented after the irrelevant movement stimulus.…”
mentioning
confidence: 98%
“…In localization tasks, a target item typically is present on each trial, and participants are required to indicate a spatial characteristic of the target (e.g., whether the target is positioned to the left or to the right of the vertical midline of the display). In such tasks, the S-R mapping can be spatially congruent (e.g., left-hand response for the left target position) or incongruent (e.g., left-hand response for right target position), with the latter inducing substantial RT costs (the Simon effect) (6,7). Note that in detection and localization tasks, it is sufficient to know either whether or where a target appeared in the display.…”
Section: Main Categories Of Visual-search Task Settingsmentioning
confidence: 99%
“…The conditional presumed ventral task (perceptual route, De Jong, Liang, & Lauber, 1994;Hommel, 1993;Kornblum, Hasbroucq, & Osman, 1990) was a motor response to a particular colour cue; for example: "press the left button on a response box if you see the fixation cross turns red". An unconditional, presumed dorsal task (action route, De Jong et al, 1994;Hommel, 1993;Kornblum et al, 1990) was a response which spatially corresponded to the stimulus location (spatial cues); for example: "press the left response box button if the fixation cross jumps to the left".…”
Section: Taskmentioning
confidence: 99%
“…An unconditional, presumed dorsal task (action route, De Jong et al, 1994;Hommel, 1993;Kornblum et al, 1990) was a response which spatially corresponded to the stimulus location (spatial cues); for example: "press the left response box button if the fixation cross jumps to the left". The interference between colour and spatial cues was measured using a redundant-target paradigm (Miller, 1982(Miller, , 1986Mordkoff & Yantis, 1993).…”
Section: Taskmentioning
confidence: 99%